A direct numerical integration scheme for visco-hyperelastic models using radial return relaxation - Lejeunes, Stéphane; Méo, Stéphane; Boukamel, Adnane (European Journal of Computational Mechanics, 2010)
In this paper, a numerical integration scheme of the evolution laws for viscohyperelastic models is proposed. The starting points of the method are the exponential mapping (Reese et al., 1998) and the radial return (Weber et al., 1990; Simo, 1988). The originality of this work lies in the substitution of a differential tensorial system by a scalar one with two equations and two unknowns and in a first order Taylor expansion of them. In this way an analytical approximated exponential solution is finally obtained.